Prevalence of hypertension and its association with anthropometric parameters in adult population of Raipur city, Chhattisgarh, India - Panda, Prem S.; Jain, Kamlesh K.; Soni, Gopal P.; Gupta, Shubhra A.; Dixit, Srishti; Kumar, Jitendra (International Journal of Research in Medical Sciences, 2017)
Background: Obesity is now an important emerging public health problem in India. It is one of the major risk factor for hypertension. Overweight persons have two to six fold increase in the risk of developing hypertension. This study was carried out with objective to find out prevalence of Hypertension and assess its association with four obesity-related indices- body mass index (BMI), waist circumference (WC), waist-to-hip ratio (WHR), and waist-to-height ratio (WHtR). Methods: A cross-sectional community-based study was done among 640 study subjects of age group 25-59 years during July 2015 to June 2016. Multi stage random sampling method was used. Data collection was done using WHO STEPS instrument V 3.1. Privacy and confidentiality of data was maintained. Data was entered in the Microsoft excel, collected data was checked for its completeness and correctness before data analysis with the help of PSPP software. Results: Prevalence of hypertension among study subjects was found to be 22.19% (142 out of 640).With respect to body mass index, waist circumference, waist hip ratio and waist height ratio, 4.38%, 64.35%, 85.33%, 76.2% were found to be obese respectively. Hypertension was strongly associated with BMI (p<0.001), waist circumference (p<0.001), waist hip ratio (p<0.05), waist height ratio (p<0.05). Out of the four anthropometric variables waist hip ratio (WHR) was most strongly associated with hypertension (β=420.236, p=0.007). Conclusions: The study shows a rising burden of hypertension among study population. As WHR is the best indicator for measuring obesity, so measurement of WHR should be made compulsory in healthy life style clinics along with other parameters.